A Five-Year strategic plan for Megawide Construction Corporation - Eunice Anne C. Akim, Karl Christopher a. Asidao, Kim Angelo L. Bagui, Jon Ehroin L. Barawid, Maricel P. Carza, Keemm Louise N. Derecho, Patricia Noelle C. Ignacio, Christine Joy R. Lacson, Laarni O. Ladines, Gilleane V. Landas, Ma. Bethina V. Minolas, 4 0 16; 5
Executive Summary: This study discusses the diagnosis of the entity's financial performance number of years. An assessment of the audited financial statements from 2016 to 2020 was conducted to further scrutinize the entity's Overall operations. The tools and ratios were used to thoroughly review the entity's financial health that is crucial in identifying its strengths. weaknesses, opportunities, and threats. Megawide Construction Corporation is one of the premier builders in the Philippine construction industry who began its operations in 1997. It specializes in progressive construction and engineering solutions that incorporate the latest techniques and technologies to produce the country's finest infrastructures throughout its business activities. The entity demonstrates its pro-people efforts through its healthy working environment and competitive compensation packages for its employees. In addition, the entity accumulated several large projects in the past years and up to this date where it has formed a strong brand of first-world quality establishments even before its partnership with the Philippine government. However, the entity is vulnerable to the liabilities that come with a weak risk management department given its centralized finance operation that impedes maximizing Megawide Construction Corporation's allocation of resources which has a domino effect across all its financial affairs. It is consistent with the entity's struggling returns, which emphasizes the imperative need to increase profits from the varying core business segments to overcome its heavy reliance on debt financing, which resulted from ineffective decision-making by limited risk experts. At the end of this study, the researchers propose implementing a restructured and decentralized finance department wherein the entity will recruit more risk management experts to abolish the ineffective practices of the past organizational structure while also diversifying their revenue streams through new partnerships with real estate developers as the main producer of precast concrete. This recommendation adheres to the improvement of Megawide Construction Corporation as a whole based on the study results.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2